Fabrication of high-performance Y2O3 stabilized hafnium dioxide refractories. Issue 4 (May 2015) - Zhao, Jiaxing; Zhang, Yujun; Gong, Hongyu; Zhang, Yubai; Wang, Xianli; Guo, Xue; Zhao, Yujun
Abstract: Y2 O3 stabilized HfO2 ceramics with 5 mol% and 8 mol% Y2 O3, respectively, were successfully fabricated by pressureless sintering at 1600 °C for 1 h. The phase distribution and transformation, microstructure, and relative density were investigated for Y2 O3 stabilized HfO2 ceramics. Cubic phase was observed in the Y2 O3 stabilized hafnium dioxide while pure HfO2 showed monoclinical phase only. The SEM images of fractured surface indicated two kinds of structures existed in modified HfO2, the solid solution region and uniform polygon grains, and some holes caused by Kirkendall effect. Refractoriness test showed that high temperature volumetric stability of the material can be effectively enhanced by adding Y2 O3 into HfO2 .